2021
DOI: 10.1101/2021.01.11.21249324
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A national survey of potential acceptance of COVID-19 vaccines in healthcare workers in Egypt

Abstract: BackgroundSince the start of COVID-19 outbreak investigators are competing to develop and exam vaccines against COVID-19. It would be valuable to protect the population especially health care employees from COVID-19 infection. The success of COVID-19 vaccination programs will rely heavily on public willingness to accept the vaccine.AimsThis study aimed to describe the existing COVID-19 vaccine approval landscape among the health care providers and to identify the most probable cause of agreement or disagreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 19 publications
7
28
1
Order By: Relevance
“…This is consistent with previous studies on Saudi HCWs (n=673) in which only about a quarter intended to have the vaccine as soon as it becomes available in the country while another quarter would delay until the vaccine safety is confirmed [3]. Similar results were shown by Egyptian HCWs (n=496), of whom 13.5% totally agreed to receive the vaccine, and 32.4% somewhat agreed [4]. In our study, 30.5% of Saudi HCWs and 24% of Egyptian HCWs were willing to receive vaccination.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with previous studies on Saudi HCWs (n=673) in which only about a quarter intended to have the vaccine as soon as it becomes available in the country while another quarter would delay until the vaccine safety is confirmed [3]. Similar results were shown by Egyptian HCWs (n=496), of whom 13.5% totally agreed to receive the vaccine, and 32.4% somewhat agreed [4]. In our study, 30.5% of Saudi HCWs and 24% of Egyptian HCWs were willing to receive vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies have assessed vaccine attitudes in HCWs before the vaccine availability and uptake [1][2][3][4][5][6][7][8][9][10][11][12][13], with the rate of reported vaccine acceptance ranging from as low as 27.7% in Congolese HCWs [7] to as high as more than 95% in a study involving HCWs from the Asia-Pacific region [10]. The HCWs were found to be more inclined to take the vaccine than non-HCWs [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for Arab countries, the more recent studies 10,14,34 show lower acceptance rates than the earlier ones. For example, A study conducted in Egypt (n=559) during March, 2020 found out that about 73.0% were looking forward to getting the vaccine when available [11][12][13] .…”
Section: Discussionmentioning
confidence: 69%
“…For example, A study conducted in Egypt (n=559) during March, 2020 found out that about 73.0% were looking forward to getting the vaccine when available [11][12][13] . However, the more recent study on HCW in Egypt (n=496) during December, 2020 concluded that only 13.5% totally agree to receiving the vaccine, and 32.4% somewhat agree 34 . In our survey that is more recent than the mentioned studies, 17.0% and 24.0% of participants in Egypt (general [n= 5,339] and HCW [n= 1,250], respectively) were willing to take the vaccine.…”
Section: Discussionmentioning
confidence: 98%